Enhancement of striatum-dependent memory by conditioned fear is mediated by beta-adrenergic receptors in the basolateral amygdala - Travis D. Goode; Kah-Chung Leong; Jarid Goodman; Stephen Maren; Mark G. Packard (Neurobiology of Stress, 2016)
Emotional arousal can have a profound impact on various learning and memory processes. For example, unconditioned emotional stimuli (e.g., predator odor or anxiogenic drugs) enhance dorsolateral striatum (DLS)-dependent habit memory. These effects critically depend on a modulatory role of the basolateral complex of the amygdala (BLA). Recent work indicates that, like unconditioned emotional stimuli, exposure to an aversive conditioned stimulus (CS) (i.e., a tone previously paired with shock) can also enhance consolidation of DLS-dependent habit memory. The present experiments examined whether noradrenergic activity, particularly within the BLA, is required for a fear CS to enhance habit memory consolidation. First, rats underwent a fear conditioning procedure in which a tone CS was paired with an aversive unconditioned stimulus. Over the course of the next five days, rats received training in a DLS-dependent water plus-maze task, in which rats were reinforced to make a consistent body-turn response to reach a hidden escape platform. Immediately after training on days 1–3, rats received post-training systemic (Experiment 1) or intra-BLA (Experiment 2) administration of the β-adrenoreceptor antagonist, propranolol. Immediately after drug administration, half of the rats were re-exposed to the tone CS in the conditioning context (without shock). Post-training CS exposure enhanced consolidation of habit memory in vehicle-treated rats, and this effect was blocked by peripheral (Experiment 1) or intra-BLA (Experiment 2) propranolol administration. The present findings reveal that noradrenergic activity within the BLA is critical for the enhancement of DLS-dependent habit memory as a result of exposure to conditioned emotional stimuli.